Parametric Study of a Two-Phase Closed Thermosyphon Loop (Journal of Engineering, 2022)
A theoretical and experimental investigation was carried out to study the behavior of a two-phase closed thermosyphon loop (TPCTL) during steady-state operation using different working fluids. Three working fluids were investigated, i.e., distilled water, methanol, and ethanol. The TPCTL was constructed from an evaporator, condenser, and two pipelines (riser and downcomer). The driving force is the difference in pressure between the evaporator and condenser sections and the fluid returns to the heating section by gravity. In this study, the significant parameters used in the experiments were filling ratios (FR%) of 50%, 75%, and 100% and heat-input range at the evaporator section of 215-860.2 W. When the loop reached to the steady-state, the wall-temperature was recorded at various positions along the thermosyphon loop. Results showed that the thermal performance with water was better than methanol and ethanol with same condition. The experimental values of the heat transfer coefficient at the evaporator section were measured for the three working fluids. The results were estimated with the nucleate boiling correlation using engineering equation solver (ESS) program. In addition, a comparison between the experimental ( ) and theoretical ( values of heat transfer coefficient in the evaporator section showed good agreement with a maximum difference of 16%.